IMPACT OF TOTAL ASSET TURNOVER RATIOS ON EQUITY RETURNS: DYNAMIC PANEL DATA ANALYSES - Patin, Jeanne-Claire; Rahman, Matiur; Mustafa, Muhammad (STIE Malangkucecwara, 2020)
This paper is an empirical exploration of the impact of total asset turnover ratios on stock returns of 1961 US public firms in different types of industries from 2001 to 2015. Stock prices are significantly influenced by operating performance of a company in efficiently utilizing its assets. For that matter, operating efficiency (as measured by total asset turnover ratio) plays a role in portfolio investment decisions. Pedroni?s heterogeneous panel co-integration procedures, associated bivariate error-correction model (ECM), dynamic ordinary least squares (DOLS) and generalized method of moments (GMM) are applied. Both stock returns and total asset turnover ratios in levels are nonstationary with I (1) behavior. Subsequently, both variables are found cointegrated. The panel ECM estimates suggest convergence of variables toward long-run equilibrium at moderate pace with short-run interactive positive feedback effects. Again, both DOLS and GMM estimates reveal short-run contemporaneous positive effects of total asset turnover ratios on stock returns in levels. In view of the findings of this study, firms should strive to improve operating efficiency, among others, to enhance competitiveness and thereby to boost their stock prices for rewarding shareholders.